1971
DOI: 10.1161/01.str.2.2.160
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Prognosis of Transient Cerebral Ischemic Attacks

Abstract: A 15-year follow-up of 140 patients who had transient cerebral ischemic attacks and were first seen at the Mayo Clinic for this complaint in 1950 through 1954 is reported. There was no significant difference in mortality related to sex or location of residence. Patients hypertensive at onset of symptoms had no significant increase in mortality compared to normotensive patients but the survival trend favored normotensive patients. Probability of surviving 15 years was significantly less than expected for patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
0
5

Year Published

1975
1975
1993
1993

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(26 citation statements)
references
References 3 publications
3
18
0
5
Order By: Relevance
“…23 The serious effect of arterial hypertension on the probability of survival was clearly demonstrated by life table analysis of our patients -this tallies with earlier observations. 7 The risk of IBI in our patients with TIA was not as severe as commonly assumed. Furthermore, TIA was more often a warning sign of AMI than a warning of IBI.…”
supporting
confidence: 50%
See 1 more Smart Citation
“…23 The serious effect of arterial hypertension on the probability of survival was clearly demonstrated by life table analysis of our patients -this tallies with earlier observations. 7 The risk of IBI in our patients with TIA was not as severe as commonly assumed. Furthermore, TIA was more often a warning sign of AMI than a warning of IBI.…”
supporting
confidence: 50%
“…These figure are somewhat better than those reported by Goldner and others. 7 One reason for this may be the younger age structure of the patients here. Females had a slightly more favorable course, confirming the report by Whisnant and others.…”
mentioning
confidence: 95%
“…14 ' 20 This also was noted in our series where equal numbers of deaths were due to cerebrovascular and coronary heart diseases. This supports the concept of universal atherosclerosis as a basic etiology in ICA occlusion.…”
Section: Discussionsupporting
confidence: 74%
“…To evaluate how well the objectives of therapy for transient focal cerebral ischemic attacks have been accomplished, it is first necessary to understand fully the variable natural history of the disorder and realize the necessity to compare the results of any form of treatment with the observations of a similar group of patients not undergoing therapy. The natural history Pearce, et al 4 Baker, et al 6 Baker, et al 6 Friedman, et al 7 Marshall 8 Ziegler and Hassanein 9 Goldner,* et al 10 Whisnant, et al 11 Marshall 12 Olsson et al 13 Number •Goldner, Whisnant and Taylor reported on 140 TIA patients followed 15'years. Table 1 gives occurrence of stroke in 111 patients' of these attacks is so variable that no significant judgment can be made about the efficacy of a therapy from simple observations of an occasional patient.…”
Section: Principles Of Therapymentioning
confidence: 99%
“…Pearce 4 and associates followed the patients for less than a year. Their results suggest that had their patients been observed for 50 to 60 months, the percentage of those developing cerebral infarction might have been the highest recorded in 10 covered a 15-year follow up of 150 patients who had transient cerebral ischemic attacks and were first seen by the Mayo Clinic for this complaint in 1950 through 1954. Follow up data were complete on only 111 patients; with data complete enough to know whether there had been a stroke or not.…”
Section: Principles Of Therapymentioning
confidence: 99%